2009
DOI: 10.1007/s11104-008-9868-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fertilizer type and rate on carbon and nitrogen pools in a sandy Cambisol

Abstract: Type and rate of fertilizers influence the level of soil organic carbon (C org ) and total nitrogen (N t ) markedly, but the effect on partitioning of C and N into different pools is open to question. Objectives were to investigate the impact of fertilizer type and rate on labile, intermediate and passive C and N pools in a sandy Cambisol at Darmstadt, Germany, after 27 years of different fertilization treatments. The six treatments were: straw incorporation plus application of mineral fertilizer (MSI) and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
4
44
1
Order By: Relevance
“…II) but depended significantly on the application rate and ranged from 7 to 13% of SOC and from 4 to 5% of total N (Heitkamp et al, 2009). In contrast, the size of the calculated intermediate C pool was greater for the manure treatments (Tab.…”
Section: And N Storage In Different Soil Fractionsmentioning
confidence: 94%
See 3 more Smart Citations
“…II) but depended significantly on the application rate and ranged from 7 to 13% of SOC and from 4 to 5% of total N (Heitkamp et al, 2009). In contrast, the size of the calculated intermediate C pool was greater for the manure treatments (Tab.…”
Section: And N Storage In Different Soil Fractionsmentioning
confidence: 94%
“…In the four-year course of the crop rotation from 2003 to 2006, measured mean annual C inputs (t ha −1 year −1 ) with straw were between 1.0 and 1.2 in the NPK and straw treatments, whereas measured differences in C inputs from manure were more pronounced and ranged from 0.6 to 1.3 in the manure treatments (Heitkamp et al, 2009).…”
Section: Darmstadt (Germany)mentioning
confidence: 99%
See 2 more Smart Citations
“…The high rates of C export support the notion that agricultural catchments, particularly pastoral systems, yield higher C losses than do forested or seminatural catchments (Graeber et al, 2012). Increased C losses from agricultural catchments may be caused by manure applications and grazing causing an increase in soil dissolved organic matter concentration through stimulation of microbial activity and increased oxygenation of the agricultural soils (Chantigny, 2003;Heitkamp et al, 2009) and higher erosion rates (Hope et al, 1997a;Quinton et al, 2010) transporting high rates of particulate C. The few studies that quantified DOC and particulate C in agricultural landscapes showed a high contribution of particulate carbon to overall C losses by low DOC/TOC ratios (up to 1.01) and 58 and 42% of organic C losses as DOC and particulate organic C, respectively (Stutter et al, 2008). Therefore, studies measuring C cycling and C losses from agricultural land to freshwater should include TC as up to 50% of C losses may not be accounted for (Quinton et al, 2006).…”
Section: How Do Rates Of Sediment and Macronutrient Delivery From Intmentioning
confidence: 78%